2011
DOI: 10.1128/iai.01282-10
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Blocking of Innate Immunity Cells by Candida albicans Chitin

Abstract: Chitin is a skeletal cell wall polysaccharide of the inner cell wall of fungal pathogens. As yet, little about its role during fungus-host immune cell interactions is known. We show here that ultrapurified chitin from Candida albicans cell walls did not stimulate cytokine production directly but blocked the recognition of C. albicans by human peripheral blood mononuclear cells (PBMCs) and murine macrophages, leading to significant reductions in cytokine production. Chitin did not affect the induction of cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
180
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(195 citation statements)
references
References 56 publications
12
180
0
3
Order By: Relevance
“…Therefore, morphological and physiological plasticity allows fungi to rapidly adapt to changing extracellular conditions. Species-specific signaling and morphological features appear to be a direct result of fungal attempts to survive as new microenvironments, and their particular cell stresses, were encountered (Hogan and Klein 1994;Newman et al 1995;Batanghari et al 1998;Sebghati et al 2000;Gow et al 2002;Brandhorst et al 2004;Rappleye et al 2004Rappleye et al , 2007Gantner et al 2005;Nemecek et al 2006;Gauthier and Klein 2008;Nather and Munro 2008;Mora-Montes et al 2011;. The concerted action of morphotype and physiological changes in the context of a particular environment are therefore critical for successful fungal adaptation (Butler et al 2009;O'Connor et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, morphological and physiological plasticity allows fungi to rapidly adapt to changing extracellular conditions. Species-specific signaling and morphological features appear to be a direct result of fungal attempts to survive as new microenvironments, and their particular cell stresses, were encountered (Hogan and Klein 1994;Newman et al 1995;Batanghari et al 1998;Sebghati et al 2000;Gow et al 2002;Brandhorst et al 2004;Rappleye et al 2004Rappleye et al , 2007Gantner et al 2005;Nemecek et al 2006;Gauthier and Klein 2008;Nather and Munro 2008;Mora-Montes et al 2011;. The concerted action of morphotype and physiological changes in the context of a particular environment are therefore critical for successful fungal adaptation (Butler et al 2009;O'Connor et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Glucans are key fungal PAMPs. 18,19,118 A recent study revealed that glucans from C. albicans hyphae are different from those from yeast cells. Hyphal glucan induces robust immune responses in human PBMCs and macrophages via a Dectin-1-dependent mechanism.…”
Section: Differential Recognition Of Yeasts and Hyphaementioning
confidence: 99%
“…On human peripheral blood mononuclear cells (PBMCs) and murine macrophages, purified chitin from C. albicans could block the recognition of C. albicans yeast cells. 19 A recent study revealed that purified chitin particles derived from C. albicans led to the selective secretion of the anti-inflammatory cytokine IL-10 on murine bone marrow-derived macrophages, 122 and NOD2, TLR9 and MR are essential fungal chitin-recognition receptors for this response. 122 The recognition of C. albicans by PRRs is generally thought to occur at the phagocytic cell surface and this process leads to the phagocytosis of C. albicans and the formation of an intracellular vacuole called phagosome.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for these disparate findings include different sources (e.g. shrimp, crab, fungal) and manufacturing processes utilized to make the glycans, resulting in variability in the tertiary structure of the polymers and in the degree of contaminants (13,19). Chitin is frequently isolated from crustacean waste products and is naturally associated with protein and minerals that are difficult to remove.…”
mentioning
confidence: 99%